Le forme della voce L'immaginario acustico nel secondo Novecento italiano - Liberti, Giuseppe Andrea (Critica Letteraria e Linguistica, 2023)
Literary writing has always found correspondences in oral performance. One could even think of writing a history of literature 'sub specie vocis'. However, it is with the technological innovations of the 20th century that this link experiences a new fortune, flanking its multiple aesthetic declinations with a growing scientific interest. The volume "The Forms of the Voice" is composed of several essays dedicated to the fraction of contemporary imagery that re-appropriates the sound dimension of poetry as well as prose. Bringing together theoretical reflection, historical and cultural description and philological analysis of case studies, these works articulate a reflection on the different expressions of the relationship between literature and orality in the second half of the 20th century.